A theology for family ministries - Anthony, Michael J.; Anthony, Michelle; Jones, Karen E., 1956-; Cardoza, Freddy; Lawson, Michael S.; Melick, Richard R.; Hamner, Curt.; Blanchette, Leon M.; Coulter, Gordon R.; Thompson, James W. (James Weldon), 1942-; Jones, Timothy P. (Timothy Paul); Stinson, Randy, 1967-; et al. (Nashville, Tenn. : B & H Academic, 2011)
With thoroughly researched input from a broad team of family experts, the book advises church and ministry leaders on how to make biblically and philosophically informed choices when reaching out to adults and children within these shifting paradigms. Emphasis is placed on what the Scriptures teach about the composition of the home, followed by discerning and hope-filled strategies for helping all families live out their God-given mandates.
Unit 1. The changing face of the North American family -- The morphing of the family / Michael J. Anthony -- The family in formational years / Karen E. Jones -- Crisis on the doorstep / Freddy Cardoza -- Unit 2. Forming a biblical theology of the family -- Old Testament teachings on the family / Michael S. Lawson -- New Testament teachings on the family / Richard Melick Jr. -- A theology of marriage / Curt Hamner -- Spiritual markers in the life of a child / Leon M. Blanchette Jr. -- A theology of grandparenting and generational faith / Gordon R. Coulter and James W. Thompson -- Family ministry models / Timothy Paul Jones and Randy Stinson -- Unit 3. Family ministries in the local church -- Equipping parents to be the spiritual leaders in the home / Michelle D. Anthony -- Children's ministry in the context of the family for spiritual formation / Michelle D. Anthony and Kit Rae -- Youth ministry from a family perspective / David Keehn.
Includes bibliographical references and indexes.
Keywords: Church work with families; Families -- Religious life; Families -- Biblical teaching